Analisis Kepatuhan Yang Dikonstruksi Pada Budaya, Kontrol Dan Pilihan Kerja Karyawan Yang Memperoleh Upah Rendah Di Cv Abee Indonesia - Difa Novita Permatasari; Chandra Fitra Arifianto (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study analyzes the construction of compliance among low-wage employees at CV Abee Indonesia through the interaction of a family-oriented organizational culture that emphasizes honesty, responsibility, and teamwork; a hierarchical control system supported by effective direct supervision; and limited employment alternatives resulting from economic cost–benefit considerations that encourage employees to remain despite minimal wages. The primary objectives of this research are to assess the level of employee compliance, identify the factors influencing organizational performance, and provide practical recommendations for human resource management. A qualitative descriptive–analytical approach was employed through in-depth interviews with six operational employees, three months of participant observation, and document analysis. The data were interpreted using Tyler’s (1990) normative compliance theory, Jensen and Meckling’s (1976) agency theory, and Coleman’s rational choice theory to examine compliance dynamics under conditions of economic constraint. The findings indicate that a supportive organizational culture and effective control mechanisms can enhance normative compliance despite low wages. Employee job choices are largely driven by financial dependence and fear of job loss rather than intrinsic commitment, resulting in compliance as a complex social construction shaped by the interaction of these three key factors. These findings offer practical implications for home industry enterprises such as CV Abee Indonesia in formulating policies that balance work discipline and employee welfare.